The Influence of Social Media Usage on Adolescents’ Legal Awareness in Paccinongang Subdistrict, Gowa Regency - M. Ali; Auliah Andika Rukman; Akbar Aba (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study aims to analyze the influence of social media usage on adolescents’ legal awareness in Paccinongang Subdistrict, Gowa Regency. The background of this research is based on the high intensity of social media use among adolescents, which has the potential to influence their understanding and legal behavior in the digital space. This study employs a mixed methods approach with a sequential explanatory design. Quantitative data were collected through questionnaires administered to 93 respondents and analyzed using simple linear regression, while qualitative data were obtained through in-depth interviews with nine informants. The results show that social media usage has a positive and significant effect on adolescents’ legal awareness (p < 0.05), with a coefficient of determination (R²) of 50.7%. Qualitative findings reveal that social media plays a role in shaping legal knowledge, attitudes, and behavior through content exposure, digital interaction, and media experience. This study concludes that social media has the potential to serve as an effective tool in enhancing adolescents’ legal awareness when utilized wisely and in an educational manner.